REALISM AND ILLUSION: AN ANALYSIS OF SANUSI’S SPEECHONGOVERNANCE AND VIEWPOINT OF ANIGERIANPOLITICIAN - ONONIWU, MARK C.; NJEMANZE, QUEEN U.; DOZIE, CHINOMSO P. (The journal of contemporary issues in business and government, 2019)
Present-day leaders and/or politicians are experts at using language to manipulate the electorate and the people they lead. This statement infers that leadership and political discourse operate indexically, in other words, every single word being used either implicitly or explicitly, expresses some political viewpoint. This could be illusionary or realistic based on how subtle people are addressed, the information provided, and the impression the speech carries based on the words used to convey the impressions. In this study, the researchers considered the different political comments inherent in the speech of Sanusi Lamido Sanusi, the Emir of Kano (henceforthreferred to as SLS), particularly at the birthday celebration of Nasir-EL-Rufai, former governor of a Northern State in Nigeria. The aim of the researcher is to find out how these utterances he made at the birthday party of his friend were able to betray and bring out to the fore, the inner struggles of his mind concerning the socio-political and economic situations in the North of Nigeria. The theory that underpins this study is the speech act theory; This theory is concerned with specific social acts performed in making utterances. This theory can be traced originally to the view expounded inAustin‘s seminal publication, ‗How to Do Things with Words‘ The analysis will be done according to Searle‘s five taxonomies of speech acts:assertive, directive, commissive, expressive, and declarative.This study significantly addressed the problems of the North from the viewpoint of the language of SLS‘s mind, and expressions, embedded in realism and illusion, and concluded by expressing the thoughts of the disgust, and visible frustrations of the situation in Northern Nigeria that have been going on over time.